Effects of nitrogen fertilizer sources and tillage practices on greenhouse gas emissions in paddy fields of central China. (November 2016) - Zhang, Z.S.; Chen, J.; Liu, T.Q.; Cao, C.G.; Li, C.F.
Abstract: The effects of nitrogen (N) fertilizer sources and tillage practices on greenhouse gas (GHG) emission have been well elucidated separately. However, it is still remained unclear regarding the combined effects of N fertilization and tillage practices on the global warming potential (GWP) and net ecosystem economic budget (NEEB) in paddy fields. In this paper, a 2-year field experiment was performed to investigate the effects of N fertilizer sources (N0, no N; IF, 100% N from chemical fertilizer; SRIF, 50% N from slow-release fertilizer and 50% N from chemical fertilizer; OF, 100% N from organic fertilizer; OFIF, 50% N from organic fertilizer and 50% N from chemical fertilizer) and tillage practices (CT, conventional intensive tillage; NT, no-tillage) on the emissions of methane (CH4 ) and nitrous oxide (N2 O), GWP, greenhouse gas intensity (GHGI), and NEEB in paddy fields of central China. Compared with N0 treatment, IF, SRIF, OF and OFIF treatments greatly enhanced the cumulative seasonal CH4 emissions (by 54.7%, 41.7%, 51.1% and 66.0%, respectively) and N2 O emissions (by 164.5%, 93.4%, 130.2% and 251.3%, respectively). NT treatment significantly decreased the GWP and GHGI compared with CT treatment. On the other hand, NT treatment significantly decreased CH4 emissions by 8.5–13.7%, but did not affect N2 O emissions relative to CT treatment. Application of N fertilizers significantly increased GWP and GHGI. It was worth noting that the combined treatment of OFIF and NT resulted in the second-highest GWP and GHGI and the largest NEEB among all treatments. Therefore, our results suggest that OFIF combined with NT is an eco-friendly strategy to optimize the economic and environmental benefits of paddy fields in central China. Although the treatment of SRIF plus NT showed the lowest GWP and GHGI and the highest grain yield among all treatments, it led to the lowest NEEB due to its highest fertilizer cost. These results indicate that the government should provide appropriate ecological compensation for this practice, which has low GHG emissions and high rice yield. Highlights: N fertilizer sources significantly affected CH4 and N2 O emissions. NT significantly decreased CH4 emissions but did not affect N2 O emissions compared with CT. The treatment of SRIF combined with NT showed the lowest GWP and GHGI, the highest grain yield, and the lowest NEEB. The treatment of OFIF plus NT exerted the second-highest GWP and GHGI and the largest NEEB.